1993
DOI: 10.1104/pp.103.3.919
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Acetyl-Coenzyme A Carboxylase Inhibitors on Root Cell Transmembrane Electric Potentials in Graminicide-Tolerant and -Susceptible Corn (Zea mays L.)

Abstract: Herbicidal activity of aryloxyphenoxypropionate and cyclohexanedione herbicides (graminicides) has been proposed to involve two mechanisms: inhibition of acetyl-coenzyme A carboxylase (ACCase) and depolarization of cell membrane potential. We examined the effect of aryloxyphenoxypropionates (diclofop and haloxyfop) and cyclohexanediones (sethoxydim and clethodim) on root cortical cell membrane potential of graminicide-susceptible and -tolerant corn (Zea mays L.) lines. l h e graminicide-tolerant corn line cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

1994
1994
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…Volunteer SR corn in soybean, however, is a new weed problem that could be difficult to control with many traditional POST volunteer corn herbicides. Initial studies conducted during the developmental phases of SR corn showed significant levels of cross-resistance to the other ACCase-inhibiting herbicides (Dotray et al 1993a;Parker et al 1990). However, little is known about the extent of cross-resistance in currently available commercial SR corn lines.…”
Section: Introductionmentioning
confidence: 99%
“…Volunteer SR corn in soybean, however, is a new weed problem that could be difficult to control with many traditional POST volunteer corn herbicides. Initial studies conducted during the developmental phases of SR corn showed significant levels of cross-resistance to the other ACCase-inhibiting herbicides (Dotray et al 1993a;Parker et al 1990). However, little is known about the extent of cross-resistance in currently available commercial SR corn lines.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the family of aryloxy phenoxyalkanoic acid compounds (including FE) produce depolarization of membrane potentials. 14 Progesterone exerts its effects via receptors in sperm, 42 so we think that capacitation is affected by FE and atrazine via destabilization of the sperm membrane potential and that a synergistic effect of either herbicide with progesterone promotes AR.…”
Section: Discussionmentioning
confidence: 99%
“…11 Fenoxaprop-ethyl (FE) is an aryloxy phenoxyalkanoic acid herbicide, a family of compounds that inhibit fatty acid biosynthesis in plant meristems, 12 affect the acetyl-CoA carboxylase enzyme, 13 and cause depolarization of membrane potentials. 14 Atrazine and FE are commonly used in the United States. 15 Few reports document the effects of FE on animal or human health.…”
mentioning
confidence: 99%
“…Using tissue culture-derived resistant and susceptible com lines, Dotray et al (20) investigated the root electrical response in the presence of 50 pM sethoxydim, haloxyfop acid, and diclofop acid buffered at pH 5 and 6 ( Table 3). They found no significant difference in E m response between the two biotypes.…”
Section: Ph-dependency Of the Membrane Responsementioning
confidence: 99%